Four new species of Psychotria (Rubiaceae) from New Caledonia, including one presumed to be extinct - Barrabé, Laure (Phytotaxa, 2014)
Psychotria (Rubiaceae) is the second largest genus of flowering plants in New Caledonia. A taxonomic revision in progress for this archipelago estimates the number of species as 81, all of them endemic, and 25 of which are new to science. Four of them are described and illustrated here: P. fambartiae, P. ireneae, P. nigotei and P. veillonii. Robust morphological characteristics were found to distinguish these four from other New Caledonian species. Psychotria veillonii, which is known only from the massif of Tiébaghi, might already be extinct as a result of intensive nickel mining in the area. According to the IUCN criteria, P. nigotei, should be considered Critically Endangered as it occurs only in two locations, which are close to one another; P. ireneae and P. fambartiae are considered Endangered and Vulnerable respectively, given their somewhat larger but limited distributions.